Doing Something 'Worthwhile': Intersubjectivity and Morality in Gap Year Narratives. Issue 4 (November 2014) - Snee, Helene
Gap years are often put forward as an opportunity to engage in individualized, reflexive, identity work. In contrast to this position, I draw upon a qualitative analysis of young people's travel blogs to highlight the tendency for gap year narratives to stick to standard scripts. Four key narratives frame gap years, which centre on making the most of time to do something worthwhile. I explore issues of intersubjectivity in the representation of gap year experiences, in terms of tacit consensus, moral boundary-drawing and reflexivity prompted by dialogue. Considering intersubjectivity in such accounts can add to our understanding of critical reflection in self-development strategies without resorting to the voluntarism of a reflexive model of identity. It also provides a critique of the individualized responsibility placed on young people to make the right choices.